Public-Private Partnership Scheme in Research and Development: A Bibliometric Study - Tiurma Melissa Rakhel; Parama Tirta WW Kusuma; Suardi Kadang (The Journal of Indonesia Sustainable Development Planning, 2021)
This article investigates the trends of scholarly publication in PPP research of R&D sector during the last three decades, including the publication patterns of the researchers' network and institutional structures. This article applies Bibliometric method by using VOSviewer to analyze and visualize scientific themes obtained from keywords ‘PPP and R&D’ through articles published in Scopus indexed journals. In mapping these keywords, this study found out that the most discussed topics include drug development, innovation policy, drug discovery, neglected tropical disease, global health, vaccines, and clinical trials. From these keywords, it could be concluded that the majority of the research areas of this topic focuses on the health sector. Lastly, this paper summarizes some future research directions and gives a recommendation. The recommendation is to make a mechanism for how PPP funding can be carried out in R&D activities. The PPP funding is not only meant for research infrastructure development but also R&D activities.